Comparative analysis of resuscitation using human serum albumin and crystalloids or 130/0.4 hydroxyethyl starch and crystalloids on skeletal muscle metabolic profile during experimental haemorrhagic shock in swine: A randomised experimental study. Issue 2 (February 2017) - Noll, Eric; Diana, Michele; Charles, Anne L.; Singh, François; Gan, Tong J.; Pottecher, Julien; Moussallieh, François-Marie; Namer, Izzie J.; Geny, Bernard; Diemunsch, Pierre
Abstract : BACKGROUND: Protection against acute skeletal muscle metabolic dysfunction and oxidative stress could be a therapeutic target in volume expansion for severely bleeding patients. OBJECTIVES: This experimental pilot study in swine aims at comparing 130/0.4 hydroxyethyl starch (HES) with 4% albumin along with crystalloid perfusion for first-line volume expansion in haemorrhagic shock with a particular emphasis on oxidative stress and muscular mitochondrial function. DESIGN: Randomised experimental study. SETTING: Digestive Cancer Research Institute Preclinical Laboratory, Strasbourg University Hospital, France, from February 2012 to June 2013. ANIMALS: Twenty large white pigs. INTERVENTION: Pressure-controlled haemorrhagic shock and volume resuscitation using either 4% human serum albumin or 130/0.4 HES along with crystalloid perfusion were performed in 20 large white pigs. MAIN OUTCOME MEASURES: Muscular biopsy of gastrocnemius muscle was performed for metabolomics screening, mitochondrial respiratory chain assessment and electron spin resonance reactive oxygen species production along with arterial and venous reactive oxygen species production at baseline, at the completion of shock, at 90 min and at 180 min after volume expansion. RESULTS: There was no difference between the two groups in measurements of skeletal muscle superoxide production. In a pooled analysis, there was a statistically significant decrease in gastrocnemius muscle creatine content from baseline to 90 min ( P  < 0.05) and 180 min ( P  < 0.05). Muscular lactate content and mitochondrial respiratory chain oxidative capacity remained constant at the respective time points. CONCLUSION: In this pilot experimental study in swine, during pressure-controlled haemorrhagic shock treated with either albumin or 130/0.4 HES in conjunction with crystalloid perfusion, skeletal muscle metabolic profile was unaltered. ETHICAL APPROVAL NUMBER: 38.2012.01.031.